THE EFFECT OF REHABILITATION EXERCISES IN AQUATIC SETTINGS ON ENHANCING THE FUNCTIONALITY OF DAMAGED ANKLE JOINTS IN YOUNG HANDBALL ATHLETES - Ali, Baha Abdul Hussein Abd (Journal Olahraga Rekat (Rekreasi Masyarakat), 2026)
Background. Sports activities serve as a significant medium for self-expression while also captivating public interest due to their inherent excitement and thrill. Consequently, these activities have experienced considerable advancement in their performance techniques and practice prerequisites. Participation in sporting activities imposes diverse stresses on muscles, joints, and ligaments, resulting in the potential for injuries of varied severity in different body regions, contingent upon the specific activity undertaken. Moreover, the direct interaction among players heightens the probability of injuries. Objectives. The aim of the study was to develop rehabilitative exercises by the use of an aquatic facility to enhance the efficiency of the injured ankle joint in the case of the young handball players. Method. The investigator applied the experimental approach that is appropriate to this issue, where the pre-test and the post-test were one-group. The sample used in the study was not random and included only young players (16-18 years old) in clubs in Maysan Governorate who were injured and performed rehabilitation exercises as a follow-up after a medical recovery period and this number constituted 8 players. Results. The results showed significant differences between the pre-test and post-test for the experimental group, favoring the post-test. The researcher attributes this improvement to the role of rehabilitation exercises in the aquatic environment that were designed and applied to individuals with ankle injuries. These exercises were organized, contributing to increased flexibility of the tissues surrounding the ankle joint, which led to improved elasticity of the ligaments and joints. The researcher attributes the improvement in injury levels to the aquatic environment, as it is considered an ideal place for muscle and joint injuries. Conclusion. The following conclusions and recommendations were the most important in the study: the use of rehabilitation exercises based on aquatic environment positively influenced the increase and the improvement of the range of motion of the ankle joint. Moreover, the use of rehabilitation exercise in water also helped in enhancing muscular strength that helps in the support of the ankle joint.